2006
DOI: 10.1103/physrevb.73.094507
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between superconductivity and ferromagnetism in epitaxialNb(110)Au(111)Fe(110

Abstract: In order to clarify the influence of ferromagnetism on superconductivity through a normal-metal layer, the superconducting properties of epitaxial Nb ( These results suggest that a new and more subtle form of quantum interference occurs in very clean trilayer systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…The order parameter in the Au enters the boundary conditions for superconductivity, hence it influences the T c as well. Yamazaki et al [6,7] also found oscillations in the critical temperatue with a period of nine layers. Our results suggest that these T c oscillations observed in that experiment may also 024514-7 be a consequence of the interplay between the quantum-well states and ferromagnetism.…”
Section: B Nb/au/fementioning
confidence: 94%
See 3 more Smart Citations
“…The order parameter in the Au enters the boundary conditions for superconductivity, hence it influences the T c as well. Yamazaki et al [6,7] also found oscillations in the critical temperatue with a period of nine layers. Our results suggest that these T c oscillations observed in that experiment may also 024514-7 be a consequence of the interplay between the quantum-well states and ferromagnetism.…”
Section: B Nb/au/fementioning
confidence: 94%
“…The experimental study of the interplay between superconductivity and magnetism has been carried out for many S/F combinations, especially for Nb/Fe systems [6,7,[50][51][52]. Hence, we apply the theory to study the system of Fe overlayers on Nb(001) with assuming exchange field in the z direction.…”
Section: A Nb/fe Bcc(001)mentioning
confidence: 99%
See 2 more Smart Citations
“…23 For example, several studies have analyzed the role of interface characteristics in S/F proximity effects by working with S/N/F structures in which a thin layer of normal metal is introduced in between the S and F materials [24][25][26][27][28] or changing surface geometry in nanostructured hybrids. 29 Also, the length scale for saturation of the proximity effect depends on the ferromagnetic layer: it changes from the range 0.1-1 nm in strong ferromagnets 4 such as Fe or Co to the range 1-10 nm in weak ferromagnets, such as Cu-Ni and Cu-Pd alloys.…”
Section: Introductionmentioning
confidence: 99%